SHOPPING EXPERIENCE AND SUBJECTIVE WELL-BEING: AN EMPIRICAL STUDY - Ananda Sabil Hussein (Journal of Indonesian Economy and Business (JIEB), 2018)
While a traditional marketer aims to enhance customer loyalty, a social marketer focuses on the creation of individual well-being. To date, some social marketing programs have been launched to enhance individual well-being. However, only a few studies have been oriented to investigate subjective well-being, in the domain of traditional marketing. Previous studies have indicated that service quality is an important determinant of subjective well-being for a service organization’s customers. However, this notion is not enough as service quality only captures performance of service in the level of attribute. For that reason, this introduces the notion of experience quality as the determinant of subjective well-being. To have a better knowledge about the relationship between these constructs, this study also inserted the notion of customer satisfaction and perceived shopping enjoyment as mediating variables. Two hundred respondents participated in this study. These respondents were recruited at department stores in Malang, a city in the Province of East Java. A self-administered survey was conducted to collect the data. A Covariance Based Structural Equation Model (CBSEM) was employed to analyze the data. The results of a Confirmatory Factor Analysis (CFA) confirmed the model proposed. The structural model showed that the experience of shopping has significant effects on customer satisfaction, perceived shopping enjoyment, and subjective well-being. However, this study failed to prove the mediating effects of customer satisfaction and perceived shopping enjoyment in the relationship between the shopping experience and subjective well-being. Upon the completion of this study, both theoretical and practical contributions were provided.